Occupational physical activity and cardiovascular disease mortality in the United States, 1988–2019 - Tong Xia; Liwei Chen; Jian Li (BMC Public Health)
Abstract Background Although leisure time physical activity (LTPA) is a beneficial factor for cardiovascular disease (CVD) mortality, relationships between occupational physical activity (OPA) and CVD mortality are inconclusive. We aimed to examine prospective associations of OPA with CVD mortality using a large representative sample of adult workers in the United States (US), and explore how socioeconomic status (SES) may influence these associations. Methods This cohort study included US workers (≥ 18 years) participating in the 1988 National Health Interview Survey (NHIS) and passively followed until December 31, 2019. Time (minutes/week) on strenuous OPA (e.g., lifting, pushing, or pulling heavy objects) was assessed at baseline by a questionnaire and categorized into 4 groups [i.e., none, low, medium, and high]. CVD mortality was identified by International Classification of Diseases, Tenth Version (ICD–10) and collected by the National Death Index database. We examined the association of OPA with CVD mortality using multivariable Cox proportional hazard regressions, controlling for age, sex, race/ethnicity, marital status, education, annual household income, occupation type, and pre-existing cardiometabolic disorders. Results In 28,604 participants (46.2% women; mean age 37.86 years), adjusted hazard ratios (95% CIs) of none, low, medium, and high OPA groups were 1.39 (1.01–1.91), 1.00 (reference), 1.18 (0.83–1.66) and 1.58 (1.12–2.22) for CVD mortality. The associations were stronger in workers with low education level (i.e., high school or less) [estimates of none, low, medium, and high OPA groups were 1.74 (1.09–2.78, P = 0.02), 1.00, 1.49 (0.92–2.42), and 1.87 (1.16–3.00)] or annual household income <$30,000 [estimates of OPA groups were 1.73 (1.16–2.56), 1.00, 1.29 (0.83–2.01), and 1.73 (1.14–2.65)]. Conclusions We observed that workers with either high or no strenuous OPA had higher CVD mortality compared to those with low strenuous OPA, demonstrating a U-shaped association in the US. This association was particularly pronounced among workers with lower SES.